PENATALAKSANAAN VULVA HYGIENE DENGAN PENYEMBUHAN LUKA PERINEUM - Dian Juni Ekasari; Prasida Yunita; Rachmawati Abdul Hafid (Universitas Batam, 2022)
Vulva Hygiene is a nursing act performed on clients who are unable to independently clean the vulva. Prevent infection in the vulvar area, perineum, or uterine. Improper treatment of perineal wounds can result in bacterial proliferation causing infection of the perineum. The purpose of this study is to obtain scientific reference sources about vulva hygiene techniques with perineal wound healing based on the results of previous studies. The research method by conducting a literature search conducted until December 2021 through a Pubmed database and google scholar using the keyword vulva hygiene used 30 articles as a reference source. Vulvar hygiene technique is something that affects wound healing. Vulva hygiene technique is very important to improve health, especially in postpartum mothers who must always maintain their hygiene in the genitalia area, especially in the wound area so that it will affect the healing process of wounds to heal normally. Many mothers do not know how to maintain their cleanliness, especially in the genitalia area. Mother only maintains her cleanliness according to her ability and knowledge by avoiding pain and fear of stitches between the anus and vagina torn. So that the mother just cleans it regardless of the way the vulva hygiene properly and correctly then the perineum stitch wound will not experience infection and will heal within 6-7 days. Health workers are advised to provide information to mothers about how to care for perineal wounds so that mothers will know how to care for perineal wounds properly.